Acute and chronic kidney disease in elderly patients with hip fracture: prevalence, risk factors and outcome with development and validation of a risk prediction model for acute kidney injury - Porter, Christine J.; Moppett, Iain K.; Juurlink, Irene; Nightingale, Jessica; Moran, Christopher G.; Devonald, Mark A.J. (BioMed Central, 2017)
Background Hip fracture is a common injury in older people with a high rate of postoperative morbidity and mortality. This patient group is also at high risk of acute kidney injury (AKI) and chronic kidney disease (CKD), but little is known of the impact of kidney disease on outcome following hip fracture.